The relation between left ventricular wall stress and QT dispersion in hypertensive urgency patients - Durukan, P; Pekdemir, M; Ozbay, Y; Karaca, I; Yildiz, M; Akbulut, M; Rahman, A (W B Saunders Co Ltd, 2004)
[Abstract Not Available]
ESC Congress 2004 -- AUG 28-SEP 01, 2004 -- Munich, GERMANY